Disciplinary And Gender Differences In Students’ Perceptions of ChatGPT For Academic Assignments: A Case of Universitas Negeri Semarang - Harwia Zahra Febriana; Limpad Nurrachmad; ⁠Dania Azzalia Wijaya; Marito Megawati Hutasoit; Vica Syah Putri Piliang (CV. ITTC INDONESIA, 2026)
The rapid adoption of generative artificial intelligence has transformed how university students approach academic tasks, making it important to understand their perceptions of tools such as ChatGPT across different academic contexts. This study investigated students’ perceptions of ChatGPT for academic assignments at Universitas Negeri Semarang, with particular attention to disciplinary and gender-related variations. Using a mixed-methods approach, data were collected through a questionnaire survey involving 40 students and semi-structured interviews with five students from different academic disciplines. The findings indicated that students generally perceived ChatGPT as a useful, accessible, and efficient academic support tool. Participants reported that ChatGPT helped them understand complex learning materials, generate ideas, organize assignment structures, improve writing processes, and enhance overall academic productivity. The findings suggested possible disciplinary variations in usage patterns, as interview participants reported utilizing ChatGPT according to specific demands of their academic fields, including brainstorming, academic writing, conceptual learning, coding assistance, and problem-solving activities. Although minor variations in usage habits were observed between male and female students, both groups demonstrated similarly positive attitudes toward AI-assisted learning. Students showed strong awareness of ethical considerations and emphasized the importance of verifying AI-generated information before incorporating it into academic work. Despite recognizing limitations such as occasional inaccuracies and contextually inappropriate responses, students viewed ChatGPT as a complementary learning resource rather than a substitute for independent thinking. The study highlights the importance of promoting responsible AI integration in higher education through digital literacy development, critical evaluation skills, and ethical guidelines for the responsible use of AI in academic contexts.